Peer-teaching program to boost English speaking skill for young learners - Alvanita Alvanita; Adi Sutrisno (University of Merdeka Malang, 2023)
The community service program (PkM) was conducted by the English Department, Faculty of Cultural Sciences, Universitas Gadjah Mada at Asrama Kinanti 1, Sleman, Special Region of Yogyakarta. This program focuses on English language teaching, specifically English Speaking. Speaking skill, especially in English, is essential for the participant’s future academic or career. It is found that the students in Asrama Kinanti 1 are required to improve their English skills and to be confident in speaking English. Therefore, the team initiated an English Conversation course to assist them. This program is held three times weekly at Asrama Kinanti 1 through a peer teaching program. Besides, native speakers are invited to boost the participants; confidence and motivation. During the program, the participants are given a module that encompasses vocabulary enrichment and a list of expressions. Then, in the class, the participants will focus on practicing what they have learned from the module. By the end of the program, the participants do a performance to show the final result. This program is proven to assist the participants to improve their English and boost their confidence due to a supportive environment between the tutors and the learners.